Shaping the Image of Tourism Destination by Network Tourism News - Min Liang (Forest Chemicals Review)
The rapid development of network age, information technology and the popularity of new media provide a new way for the dissemination of tourism news and affect the development of tourism economy. This paper mainly explores the influence of images and images in online tourism news on the cognitive image and emotional image of tourist destinations, and then constructs a new tourist destination image. This paper analyzes the content and form of online tourism news through theoretical and literature discussion, and analyzes the formation and change of tourist destination image constructed by tourism news from the aspects of image science, communication science and psychology. Then through the comparison of similar tourist destination image to obtain its unique, as a tourist destination image communication basis.